Hemorrhage of the Ramus Lumbalis of the Iliolumbar Artery as a Cause for Shock in Blunt Trauma Victims on Therapeutic Anticoagulation - Thomas Patrick Sullivan; Eduardo Smith-Singares (Case Reports in Surgery)
Noncavitary torso hemorrhage is a rare and poorly characterized injury that can lead to exsanguination if not promptly addressed. When present in a high-risk patient on therapeutic anticoagulation, it can lead to a swift fatal outcome. Two cases (an 80-year-old female on warfarin and a 67-year-old male on apixaban for atrial fibrillation) presented with shock after direct blunt trauma in their torsos. Embolotherapy techniques were utilized to obtain angiostasis while the patients were resuscitated with massive transfusion protocols and reversal of the agents received. In the setting of severe localized blunt trauma on an aging victim while on antithrombotic medications, noncavitary torso hemorrhage must be included in the differential diagnosis. Local expertise and a high level of suspicion were critical in the early intervention, and postprocedural management of the injuries sustained and secured a good result.